2014
DOI: 10.1371/journal.pone.0087288
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Analysis of Thumb Opponency Movement in the Capuchin Monkey (Sapajus sp)

Abstract: Capuchin monkeys present a wide variety of manipulatory skills and make routine use of tools both in captivity and in the wild. Efficient handling of objects in this genus has led several investigators to assume near-human thumb movements despite the lack of anatomical studies. Here we perform an anatomical analysis of muscles and bones in the capuchin hand. Trapezo-metacarpal joint surfaces observed in capuchins indicate that medial rotation of metacarpal I is either absent or very limited. Overall, bone stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(58 citation statements)
references
References 23 publications
4
54
0
Order By: Relevance
“…When the anatomical data are applied to evolutionary, taxonomy and phylogenetic studies, errors could be propagated indefinitely and incorrect conclusions and hypothesis will be obtained (AVERSI-FERREIRA et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When the anatomical data are applied to evolutionary, taxonomy and phylogenetic studies, errors could be propagated indefinitely and incorrect conclusions and hypothesis will be obtained (AVERSI-FERREIRA et al, 2014a).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, anatomical structures of bearded capuchins seem to be closer to those of other New World primates, per its taxonomy, but few studies on its anatomy are reported (AVERSI-FERREIRA et al, 2014a). Nevertheless, in recent years some, but not enough, works about Sapajus anatomy associated with its behavioral aspects were performed.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations